Distribution. Cold temperate to subarctic waters of the N Atlantic Ocean (including mouth of the Saint Lawrence River, Canada, but excluding the Baltic Sea), S to ¢.38° N in W Atlantic Ocean, and from S Svalbard to the Brittany coast, France, in the E Atlantic Ocean. in Delphinidae - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
Distribution. Cold temperate to subarctic waters of the N Atlantic Ocean (including mouth of the Saint Lawrence River, Canada, but excluding the Baltic Sea), S to ¢.38° N in W Atlantic Ocean, and from S Svalbard to the Brittany coast, France, in the E Atlantic Ocean. Published as part of Russell A. Mittermeier & Don E. Wilson, 2014, Delphinidae, pp. 410-526 in Handbook of the Mammals of the World – Volume 4 Sea Mammals, Barcelona :Lynx Edicions on page 489, DOI: 10.5281/zenodo.6610922